Booked - Alexander, Kwame (Houghton Mifflin Harcourt, 2016)
Twelve-year-old Nick loves soccer and hates books, but soon learns the power of words as he wrestles with problems at home, stands up to a bully, and tries to impress the girl of his dreams.